A new section in the discussion, after World War - García González, Aurora (Historia y Comunicación Social, 2014)
Six years after the end of World War that faced for the first time the European powers on a global scale conflict, the newspaper El Debate, owned by the Catholic Publisher since 1912 and under the direction of Angel Herrera, began a regular column under a double title (“from British politics” and “Figures of the English Parliament”) began offering a series of commentaries on political issues from Britain. This reference is significant, despite the lack of historical perspective at the time, as it showed some shift in the stance of the newspaper. This newspaper hired a collaborator in Liverpool.